2021
DOI: 10.1039/d1ra02800f
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ag nanoparticles anchored on protonated g-C3N4–Bi2MoO6 nanocomposites for effective antibiotic and organic pollutant degradation

Abstract: The development of noble metal-anchored semiconductors for photocatalytic processes is now garnering interest for potential application to toxic pollutants as well as antibiotic degradation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…As shown in Figure a,b, bare ZrO 2 can be coded for tetragonal (JCPDS card 79-1769); its fundamental diffraction patterns at 24.2, 28.2, 31.5, 34.1, 35.3, 40.7, 50.1, and 55.3° can be assigned to (011), (111), (111), (002), (211), (202), (013), and (131) planes, respectively. The firm and spire diffraction peaks of ZrO 2 confirm the high purity and crystallinity of the sample. , The primary peaks of bare g-C 3 N 4 are located at 13.1 and 27.4°, respectively, and correspond to the crystal planes (100) and (002) . It has been observed that there are no distinctive peaks of g-C 3 N 4 and MoS 2 in the ZrO 2 @MoS 2 /g-C 3 N 4 nanocomposite (Figure a,b) even though these peaks can be seen in the transmission electron microscopy (TEM) pictures.…”
Section: Resultsmentioning
confidence: 72%
“…As shown in Figure a,b, bare ZrO 2 can be coded for tetragonal (JCPDS card 79-1769); its fundamental diffraction patterns at 24.2, 28.2, 31.5, 34.1, 35.3, 40.7, 50.1, and 55.3° can be assigned to (011), (111), (111), (002), (211), (202), (013), and (131) planes, respectively. The firm and spire diffraction peaks of ZrO 2 confirm the high purity and crystallinity of the sample. , The primary peaks of bare g-C 3 N 4 are located at 13.1 and 27.4°, respectively, and correspond to the crystal planes (100) and (002) . It has been observed that there are no distinctive peaks of g-C 3 N 4 and MoS 2 in the ZrO 2 @MoS 2 /g-C 3 N 4 nanocomposite (Figure a,b) even though these peaks can be seen in the transmission electron microscopy (TEM) pictures.…”
Section: Resultsmentioning
confidence: 72%
“…The catalyst's crystalline structure and morphological characteristics are not lost after numerous cycles, as shown by XRD patterns and SEM images of both fresh and used nanocrystals. 39 The 0.06 M Mg-Sr codoped ZnO photocatalyst was shown to be stable after repeated use since all of the diffraction peaks of the reused 0.06 M Mg-Sr codoped ZnO photocatalyst were in good agreement with those of the fresh 0.06 M Mg-Sr codoped ZnO photocatalyst (Fig. 1).…”
Section: Stabilitymentioning
confidence: 79%
“…The XRD patterns and SEM images of the fresh and recycled samples show that the crystallinity and morphological characteristics of the catalyst are unchanged even after five runs. 76 Table 3 compares the highest degradation capacities of EY to published values of degradation % for other catalysts. Cu–Co 3 O 4 had greater maximal degradation capacities for EY at 300 min than other materials, which might be attributed to its larger specific surface area and band gap alignment.…”
Section: Evaluation Of the Photocatalytic Activitymentioning
confidence: 99%
“…The XRD patterns and SEM images of the fresh and recycled samples show that the crystallinity and morphological characteristics of the catalyst are unchanged even after five runs. 76…”
Section: Charge Transfer Mechanism In the Photocatalystmentioning
confidence: 99%